Attempt of analysis of the functional state of modern students of technical higher educational establishment. - Kopa V.M (Kharkov National Pedagogical University, 2012)
The functional state of students of higher educational establishment - general and special medical separation on employments on physical education is considered. 31 student of general separation and 56 students of the special medical separation took part in an experiment (age 17-20 years). Such indexes of the cardiovascular system, as coefficient of economized of circulation of blood, vegetative index of Kerdo, minute volume of blood, are investigational. It is set that adaptation of vagetonic to the dosed physical loading is more high, than at symbatotonic. On the absolute values of violation of economized of circulation of blood at vagetonic less than, than in symbatotonic. On the analysis of coefficient of economized of circulation of blood about 87% students of medical separation and 67% general separation have violation of economized of circulation of blood of the cardiovascular system. The formula of index of adaptation is offered in relation to the physical loading. It is set that among the students of task medical force of violation of economized of circulation of blood among vagetonic have 100% tested persons, among symbatotonic are 86% persons (from them 2% youths and 98% girls). Among normatonic are 85% students.